2019
DOI: 10.1161/hypertensionaha.119.13184
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Identifies Placental Dysfunction and Confirms Flt-1 (FMS-Like Tyrosine Kinase Receptor 1) Biomarker Specificity

Abstract: Clinical end-stage parameters define the pregnancy disorders preeclampsia and fetal growth restriction while classification of the underlying placental dysfunction is missing and urgently needed. Flt-1 (FMS-like tyrosine kinase receptor 1) is the most promising placenta-derived predictive biomarker for preeclampsia. We aimed to classify placental dysfunction in preeclampsia and fetal growth restriction at delivery by metabolic profiling and authenticate the biomarker Flt-1 for placental dysfunction. We studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 34 publications
1
17
1
Order By: Relevance
“…The bioinformatics website suggested that FLT1 is a potential target of miR-373 ( Figure 4A ), in agreement with results showing that FLT1 expression enhances the likelihood of PE [ 14 ]. The expression of FLT1 was much higher in PE than in control rats ( Figure 4B ).…”
Section: Resultssupporting
confidence: 85%
“…The bioinformatics website suggested that FLT1 is a potential target of miR-373 ( Figure 4A ), in agreement with results showing that FLT1 expression enhances the likelihood of PE [ 14 ]. The expression of FLT1 was much higher in PE than in control rats ( Figure 4B ).…”
Section: Resultssupporting
confidence: 85%
“…The heterogeneous disorder preeclampsia consists of distinct subtypes that go beyond the current diagnostic measures. 22,47 Different ongoing pathologic processes at the maternal-fetal interface might…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneous disorder preeclampsia consists of distinct subtypes that go beyond the current diagnostic measures 22,47 . Different ongoing pathologic processes at the maternal‐fetal interface might give the same clinical symptoms in the preeclamptic mother and a better classification of the disorder taking placenta dysfunction into account would lead to improved understanding, screening, and treatment of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to another study, metabolomics placental profiles could also be useful in identifying PE with placental dysfunction and even associated IUGR [46].…”
Section: Metabolomics In Obstetricsmentioning
confidence: 99%